A comfortable combined way of assessment of colorectal anastomosis - Kononenko, I. E.; Кононенко, Ігор Євгенійович (НУОЗ ім. П. Л. Шупика, 2022)
Objective: to investigate the results of visual assessment of colorectal anastomosis (CA) with the implementation of a scoring system for laparoscopic resection of the sigmoid colon.
Зручний комплексний метод оцінки характеристик колоректального анастомозу